Pengaruh Resiliensi dan Kebahagiaan Terhadap Kinerja Perawat Melalui Kepuasan Kerja sebagai Variabel Intervening pada Rumah Sakit PKU Muhammadiyah Wonogiri - Dherisma; Putri Oktovita Sari (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study was designed to examine the relationship between resilience (X₁) and happiness (X₂) on nurse performance (Y), with job satisfaction (Z) as a mediator. The methodology used was a quantitative survey of 45 nurses at PKU Muhammadiyah Wonogiri Hospital, with data analysis using SEM-PLS. The results of the study concluded as follows: (1) There is a positive and significant direct effect of resilience and happiness on job satisfaction. (2) There is a positive and significant direct effect of resilience and happiness on nurse performance. (3) There is a positive and significant direct effect of job satisfaction on nurse performance. (4) However, the role of job satisfaction as a mediating variable was not proven to be significant; the indirect effect of resilience and happiness on performance through job satisfaction was not statistically significant.